1995
DOI: 10.2337/diab.44.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Endothelin-1 Levels in Obese Hypertensive and Normotensive Men

Abstract: Plasma endothelin-1 (ET-1) levels were studied in 15 obese hypertensive (mean age 48.5 +/- 3.9 years) and 15 obese normotensive men (mean age 49.5 +/- 3.6 years) before and after weight loss due to an 800 kcal/day diet lasting 12 weeks. Circulating peptide concentrations were also assessed in nonobese hypertensive (n = 11) and normotensive men (n = 12). Baseline plasma ET-1 levels were similar in obese hypertensive (0.87 +/- 0.22 pg/ml) and obese normotensive men (0.91 +/- 0.30 pg/ml). In seven obese hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 0 publications
1
43
0
1
Order By: Relevance
“…Although in the normal physiologic state, insulin stimulates NO synthesis and enhances NO-mediated vasodilatation, this action is blunted or reversed in the IR state [28,29]. Although the precise mechanism by which IR and hyperinsulinemia produces ED remains to be elucidated, it has been suggested that, in addition to the decreased synthesis and responsiveness of NO, IR is associated with increased production of endothelin-1, which may not only cause vasoconstriction, but probably also plays an important role in the development of hypertension frequently seen in patients with MS and DM [28][29][30].…”
Section: Endothelial Dysfunction In Metabolic Syndromementioning
confidence: 97%
“…Although in the normal physiologic state, insulin stimulates NO synthesis and enhances NO-mediated vasodilatation, this action is blunted or reversed in the IR state [28,29]. Although the precise mechanism by which IR and hyperinsulinemia produces ED remains to be elucidated, it has been suggested that, in addition to the decreased synthesis and responsiveness of NO, IR is associated with increased production of endothelin-1, which may not only cause vasoconstriction, but probably also plays an important role in the development of hypertension frequently seen in patients with MS and DM [28][29][30].…”
Section: Endothelial Dysfunction In Metabolic Syndromementioning
confidence: 97%
“…Elevated circulating levels of ET-1 have been reported in most [55, 56, 57, 58, 59, 60, 61]but not all [62, 63]studies of human insulin resistance. The ET-1 elevation has been reported to be proportional to the hyperinsulinemia [64, 65, 66], and a dietary weight loss can reduce both serum insulin and ET-1 concentrations [67]. Furthermore, acute endogenous and exogenous elevations in circulating insulin levels in normal controls and in insulin-resistant subjects have been shown to acutely elevate circulating ET-1 [56, 68, 69], although again dissenting findings exist [70, 71, 72].…”
Section: The Hyperinsulinemia Questionmentioning
confidence: 99%
“…Eine verän-derte Kontraktilität der Gefäße, insbesondere gegen vasokonstriktorische Faktoren, ist infolge veränderter intrazellulärer Elektrolytkonzentrationen postuliert worden. Dementsprechend ist interessanterweise gefunden worden [10], daß die Plasmaspiegel des Vasokonstriktors Endothelin-1 bei Adipositas erhöht sind und daß die periphere Gefäßresistenz bei adiopösen Probanden vermindert ist. Ferner ist gezeigt worden, daß die wahrscheinlich Endothel-vermittelte Stickstoffoxid-abhän-gige vasodilatatorische Wirkung von Insulin [2] bei adipösen Probanden deutlich vermindert bzw.…”
Section: Pathophysiologieunclassified